Identifikasi Keterdapatan Mineral Radioaktif pada Urat-Urat Magnetit di Daerah Ella Ilir, Melawi, Kalimantan Barat - Ngadenin; Indrastomo, Frederikus Dian; Widodo; Widana, Kurnia Setiawan (BRIN Publishing, 2019)
Ella Ilir administratively located in Melawi Regency, West Kalimantan. Regional geology of Ella Ilir area is composed of metamorphic rocks in Triassic–Carboniferous age which are intruded by Jurassic and Cretaceous granitic rocks. Radioactive minerals occurences in the area are indicated by magnetite veins radioactivities on Triassic to Carboniferous metamorphic rocks whose values range from 1,000 c/s to 15,000 c/s. Goal of the study is to determine the type of ore mineral deposits and to identify the presence of radioactive mineral in magnetite veins in Ella Ilir area. The methods used are geological mapping, radioactivity measurements, analysis on uranium grades, and mineragraphy analysis of severe magnetite veins samples. Lithologies of the study area are composed by biotite quartzite, metatuff, metasilt, metapellite, biotite granite, and ryolite. The east-west sinistral fault and the north-south dextral fault are the developed fault structures in this area. Mineral composition of magnetite veins are consists of iron ore, sulfide, and radioactive minerals. Iron ore mineral consists of magnetite, hematit, and goetite. Sulfide minerals consist of pyrite, pirhotite, and molybdenite, while radioactive minerals consist of uraninite and gummite. The occurences of magnetite veins are controlled by lithology and geological structures. The magnetite veins in metasilt are thick (1.5–5 m), filled the fractures in the fault zone. Meanwhile, the magnetite veins in metapellite are thinner (milimetric–centimetric), filled the fractures that are parallel to the schistocity. The ore deposits in the study area are iron ore deposits or magnetite ore deposits formed by magmatic hydrothermal processes.